2019
DOI: 10.12659/msm.912109
|View full text |Cite
|
Sign up to set email alerts
|

The Octamer-Binding Transcription Factor 4 (OCT4) Pseudogene, POU Domain Class 5 Transcription Factor 1B (POU5F1B), is Upregulated in Cervical Cancer and Down-Regulation Inhibits Cell Proliferation and Migration and Induces Apoptosis in Cervical Cancer Cell Lines

Abstract: Background The POU domain class 5 transcription factor 1B (POU5F1B), is a pseudogene that is homologous to octamer-binding transcription factor 4 (OCT4), and is located adjacent to the MYC gene on human chromosome 8q24. POU5F1B has been reported to be transcribed in several types of cancer, but its role in cervical cancer remains unclear. This study aimed to investigate the expression and function of POU5F1B in tissue samples of human cervical cancer and in cervical cancer cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Worldwide, cervical cancer is the second most common malignancy in women, after breast cancer, and has a high mortality rate [1–3]. Currently, there are many treatment approaches, including surgery, chemotherapy, and radiotherapy, but these are not always satisfactory, particularly in late-stage cervical cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, cervical cancer is the second most common malignancy in women, after breast cancer, and has a high mortality rate [1–3]. Currently, there are many treatment approaches, including surgery, chemotherapy, and radiotherapy, but these are not always satisfactory, particularly in late-stage cervical cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al (2017c) showed that RSU1P2 was increased in cervical cancer and boosted the malignant phenotype of cervical cancer. POU5F1B was also reported to be upregulated in cervical cancer tissues and cell lines by Yu et al (2019). The authors confirmed that interference with expression of POU5F1B significantly suppressed cell proliferation, migration and invasion, and induced apoptosis in cervical cancer .…”
Section: Other Types Of Cancermentioning
confidence: 69%
“…GBP1P1 and PTTG3P were observed in microarray analysis and validated by qRT-PCR in tissues of cervical carcinoma [46]. FTH1P3 and POU5F1B are upregulated in cervical cancer patient samples and cell lines [47,48]. In colon cancer tissues, DUXAP8, RP11-54H7.4, and RP11-138J23.1 show elevated expression in advanced tumor stages [49].…”
Section: Cancers Located In the Abdomen And Bonesmentioning
confidence: 82%